Politics across the Hudson : the Tappan Zee megaproject - Plotch, Philip Mark, 1961- (Rutgers University Press, 2018)
Politics Across the Hudson offers a behind-the-scenes look at three decades of contentious planning for the new Tappan Zee Bridge, and includes a new epilogue and more photos, revealing valuable lessons for those trying to tackle complex public policies. Drawing on his own extensive experience in planning megaprojects, more than one hundred exclusive interviews with key figures (including three governors), and extensive research into government records, Philip Plotch tells the compelling, behind-the-scenes story of high-stakes battles between powerful players in the public, private, and civic.